Perbedaan Defleksi Kawat Ortodonti Nikel-Titanium dan NiTi Epoxy Resin Coated pada Perendaman dalam Saliva Buatan dan Minuman Berkarbonasi (The Difference in Deflection of Nickel Titanium Archwire and NiTi Epoxy Resin Coated Immersed by Artificial Saliva - Citra Ayu Mawaddah; Leliana Sandra Devi A. P; Dwi Prijatmoko (Pustaka Kesehatan, 2016)
Background: Deflection of orthodontic wire can be changed by oral condition, for exampleacidic condition caused by carbonated drink consumption. Objective: to analyze the differencein deflection of Nickel-Titanium archwire and NiTi epoxy resin coated immersed by artificialsaliva and carbonated drink. Materials and Methods: This research used four sample groups:NiTi non coated archwire immersed by saliva, NiTi non coated archwire immersed by salivamixed carbonated drink, NiTi coated archwire immersed by saliva, and NiTi coated archwireimmersed by saliva mixed carbonated drink. The samples were immersed for 3.5 hours at 37° Cin incubator. The deflection was measured with Three Point Bending method using UniversalTesting Machine. Result and Conclusion: One Way Anova test result showed significantlydifference between coated and non coated group that immersed by saliva with the groupimmersed by saliva mixed carbonated drink. In conclusion, the deflection of Nickel-Titaniumarchwire and NiTi epoxy resin coated archwire had decreased after immersed by carbonateddrink and Nikel-Titanium archwire had higher deflection than NiTi epoxy resin coated immersedby artificial salivaKeywords: Carbonated Drink, Deflection Force, NiTi Archwire, NiTi Epoxy Resin CoatedArchwire